Gastric greater curvature plication combined with Nissen fundoplication in the treatment of gastroesophageal reflux disease and obesity - Ospanov, Oral; Maleckas, Almantas; Orekeshova, Akzhunus (Medicina, 2016)
Background and aim: Established anti-reflux procedures such as fundoplications are less efficient in obese patients. The aim of this study was to investigate clinical effectiveness of the fundoplication combined with gastric greater curvature plication in the treatment of gastroesophageal reflux disease (GERD) in obese patients. Materials and methods: During the period from June 2010 to September 2014, patients operated for GERD with BMI from 30 to 39.9 kg/m2 were included into the prospective study. Laparoscopic Nissen fundoplication (LNF, n = 58) was performed until February 2013 and later laparoscopic Nissen fundoplication was combined with gastric greater curvature plication (LNFGP, n = 56). The groups were compared according to the control of GERD and weight loss. Results: In LNF group there were significantly more males, patients had lower BMI and longer duration of GERD symptoms. Duration of surgery was significantly longer in LNFGP group, 96.5 (17.3) min vs. 59.8 (16.1) min (P < 0.0001). Postoperative morbidity was similar, 3.6% and 3.4% in LNFGP and LNF groups, respectively (P = 0.9539). The average percentage of excess BMI loss after 12 months was 45.3 (5.8) in LNFGP group as compared to 18.4 (4.6) in LNF group (P < 0.0001). Significantly more patients experienced remission or improvement of type 2 diabetes mellitus (P = 0.03) and hypercholesterolemia (P = 0.0001) in LNFGP group. No significant differences between the groups in postoperative DeMeester score, GERD-HRQL mean score, overall satisfaction and healing of esophagitis were observed.
Keywords: Gastroesophageal reflux disease; OBESITY; Nissen fundoplication; Gastric greater curvature plication